The development of mathematical model for the study of electromagnetic interference from the traction converters with asynchronous motor - Shcheka, V. I.; Havryliuk, V. I. (Science and Transport Progress, 2010)
The mathematical modeling and circuit simulation of asynchronous propulsion drive unit with converters on IGBT transistors have been made. The possible noises appearing during drive’s operation have been determined. The spectral composition of phase current of the asynchronous engine has been obtained.